2001
DOI: 10.32420/2002.21.1235
|View full text |Cite
|
Sign up to set email alerts
|

Socio-psychological view on the modern charismatic movement

Abstract: The emergence and activity of neo-religious groups, to which we also refer to charismatic churches, is a manifestation of one of the global trends of modern religious life-traditional encounter with a new, still unknown. Therefore, it is quite natural that this contact within the framework of the modern charismatic movement - this complex, multifaceted phenomenon, requires a comprehensive study, in particular philosophical, sociological, religious, theological, etc. No less relevant is the psychological approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Thus, the study showed the importance and strength of interpersonal communication, family ties, high civic position and faith in the Armed Forces of students and teachers, motivation for work, creativity and restoration of the state. Such results can be an illustration of the so-called post-traumatic growth (Tedeschi, 2004;Tytarenko, 2019). However, this hypothesis needs further clarification and verification.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the study showed the importance and strength of interpersonal communication, family ties, high civic position and faith in the Armed Forces of students and teachers, motivation for work, creativity and restoration of the state. Such results can be an illustration of the so-called post-traumatic growth (Tedeschi, 2004;Tytarenko, 2019). However, this hypothesis needs further clarification and verification.…”
Section: Discussionmentioning
confidence: 87%
“…Соціальний і психологічний аспекти відновлення, які є невід'ємними складовими людської особистості, до останнього часу бралися до уваги дуже рідко. Хоча саме вони є надзвичайно важливими, бо якщо медична реабілітація відновлює втрачені функції і властивості організму людини, то соціально-психологічна реабілітація забезпечує нормальне існування особистості в соціумі, її повноцінну соціальноекономічну інтеграцію, відновлення психо-емоційної рівноваги [11,18].…”
Section: актуальність дослідження визначаютьunclassified
“…П'ята проблема -відсутність чітких науково обґрунтованих рекомендацій щодо архітектурного формування центрів соціально-психологічної реабілітації. Йдеться, насамперед, про дослідження відповідності функціональної і композиційно-планувальної структури реабілітаційного центру певній цільовій категорії користувачів, аналіз їхніх потреб і необхідних умов [18].…”
Section: актуальність дослідження визначаютьunclassified
See 1 more Smart Citation